PERSEPSI RISIKO DAN KECENDERUNGAN RISIKO INVESTOR INDIVIDU - Wiwik Lestari; Rr. Iramani Iramani (University of Merdeka Malang, 2013)
The two important measurements of risks on behavioral point of view were risk perception and risk propensity.The two construct hypothesizes had negative relationship. This study attempted to establish a model by whichto measure those attitudes towards investment risk and also examined some variables that were postulated asexternal factors of investor investment decision. External factors were the availability of information, socialinteraction, financial adviser and familiarity. The data were collected on a survey research to 150 investors asrespondents in Surabaya area. By employing GeSCA, the result showed that risk propensity and risk perceptionhad negative correlation, supporting previous studies on this two variables relationship. This study alsoproved that external factor significantly affected risk perception and risk propensity